Penerapan Relaksasi Otot Progresif untuk Meningkatkan Kualitas Tidur pada Remaja Awal - Mudrikaturobiah, Ika; Shufah, Imas; Sundari, Ririn Isma; Rahmawati, Arni Nur (Yayasan Inspirasi El Burhani, 2025)
Introduction: Sleep is a fundamental need for adolescents, yet many experience poor sleep quality due to stress, academic workload, and excessive smartphone use. Such disturbances often lead to decreased concentration and reduced academic performance. Objective: The purpose of this service was to improve the sleep quality of early adolescents at MTs Miftahul Ulum Karangpari, Brebes, through the application of progressive muscle relaxation (PMR) techniques as a nonpharmacological intervention. Method: This public service was conducted in two sessions involving 13 eighth-grade students. Activities included counseling, demonstrations, and practice of PMR techniques. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention to assess changes in participants’ sleep patterns. Result: The findings showed a notable improvement in sleep quality after the intervention. Before the program, 53.84% of participants had poor sleep quality, 23.08% moderate, and 23.08% good. After implementing PMR, 46.15% achieved good sleep quality, 46.15% moderate, and only 7.70% remained in the poor category. The results indicate an overall improvement of three participants moving to the good category and a reduction of six participants from the poor category. Conclusion: The findings showed a notable improvement in sleep quality after the intervention. Before the program, 53.84% of participants had poor sleep quality, 23.08% moderate, and 23.08% good. After implementing PMR, 46.15% achieved good sleep quality, 46.15% moderate, and only 7.70% remained in the poor category. The results indicate an overall improvement of three participants moving to the good category and a reduction of six participants from the poor category.